2002
DOI: 10.1046/j.1529-8817.2002.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

POLYAMINES INFLUENCE MATURATION IN REPRODUCTIVE STRUCTURES OF GRACILARIA CORNEA (GRACILARIALES, RHODOPHYTA)1

Abstract: Naturally occurring levels of putrescine, spermidine, and spermine were analyzed in female gametophyte (nonfertilized) and reproductive tissues (cystocarps) at two different stages of development in the marine red algae Gracilaria cornea J. Agardh. Endogenous polyamine levels changed at differential stages of cystocarp maturation. Highest polyamine values were found on tissue from the early post‐fertilization stage, decreasing as the cystocarp matured. Incubation experiments revealed that exogenous polyamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 41 publications
2
50
0
1
Order By: Relevance
“…Ethylene has been reported to induce tetrasporogenesis in Pterocladiella capillacea (García-Jiménez and Robaina 2012). The maturation, liberation, and growth of carpospores in Grateloupia imbricata and Hydropuntia cornea (Guzmán-Urióstegui et al 2002, Sacramento et al 2004a, on the other hand, have been shown to be stimulated by polyamines.…”
Section: Endogenous Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene has been reported to induce tetrasporogenesis in Pterocladiella capillacea (García-Jiménez and Robaina 2012). The maturation, liberation, and growth of carpospores in Grateloupia imbricata and Hydropuntia cornea (Guzmán-Urióstegui et al 2002, Sacramento et al 2004a, on the other hand, have been shown to be stimulated by polyamines.…”
Section: Endogenous Signalingmentioning
confidence: 99%
“…Additional insights have been provided by transcriptomic analyses in a number of species, including Pyropia (Uji et al 2013) and Gracilariopsis (Kamiya et al 2011), which have identified sets of genes upregulated in different phases of the life cycle. In Gracilaria, Hydropuntia and Grateloupia, research has focused on the ornithine decarboxylase GiODC gene, which regulates carpospore maturation and liberation (Guzmán-Urióstegui et al 2002, Sacramento et al 2004b, García-Jiménez et al 2009, reviewed in García-Jiménez and Robaina 2015. Variation in the expression of GiODC was observed during cystocarp development with levels reduced in fertile tissue (García-Jiménez et al 2009).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…From our results carpospores treated with Pas had increased numbers and lengths of apical meristem inducing multiaxial growth particularly with Spm (10 -6 M) and treatment C3. Guzmán-Urióstegui et al (2002) reported a sharp increase in endogenous levels of PAs during cystocarp development at early post-fertilization events as opposed to the PAs found in female thalli without fertilized carpogonia and mature cystocarp. Sacramento et al (2007) also reported that infertile axes from Grateloupia gametophyte thalli accumulated more PAs than those axes with cystocarps.…”
Section: Discussionmentioning
confidence: 83%
“…Due to the impossibility of direct sterilization of carpospores, the sterilization protocol used the cystocarp, the reproductive body in red algae developed after fertilization consisting of a conceptacle bearing the carpospores. Thus, mature cystocarps were selected according to the description by Guzmán-Urióstegui et al (2002), excised from thalli (3-4 cm length), immersed 10 s in 0.5% iodine solution, and later immersed 10 s in 0.5% sodium hypochlorite. Cystocarps were incubated for 24 h in 10 ml sterilized seawater with penicillin (1,000 mg l -1 ), ampicillin (250 mg l -1 ), nystatin (250 mg l -1 ) and germanium dioxide (100 mg l -1 ).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation